English Language Learning of Indonesian Students during Study Abroad Program in Australia - Sabaruddin Sabaruddin (Institut Agama Islam Negeri Palopo, 2019)
This article discusses how the transformation of identity and cultural learning influence the English language learning of Indonesian students during their study program. This article is divided into three different sections of discussions in order to elaborate this issue comprehensively. Firstly, the identity change during the study abroad program is discussed by utilising the concept of identity. Subsequently, the process of identity transformation of Indonesian students during their study abroad is further elaborated through the identity movement theory. Secondly, the process of cultural learning during study abroad program is explained regarding English language learning of Indonesian students. Thirdly, how the students’ identity transformation and cultural learning impact on English language learning is also be analysed. In conclusion, the role of identity transformation and intercultural learning is significant in the enhancement of English language proficiency of the students during the study overseas program. Furthermore, the process of English language learning transforms the students’ identities through the students’ engagement in the new sociocultural condition. The transformation of students’ identity occurs in three steps of identity movement which are molar, molecular and line of flight identity. The transformation also lies in intercultural learning which later develops the students’ intercultural awareness and understanding. That is to say, study overseas can transform the students’ identity and facilitate cultural learning in which both are beneficial in enhancing the English language proficiency of the student. Besides that, study abroad program also constructs difference between individuals who pursue study overseas and who do not.